2012
DOI: 10.1007/s11442-012-0921-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal trend and statistical distribution of extreme precipitation events in Huaihe River Basin during 1960–2009

Abstract: Based on the daily precipitation data of 27 meteorological stations from 1960 to 2009 in the Huaihe River Basin, spatio-temporal trend and statistical distribution of extreme precipitation events in this area are analyzed. Annual maximum series (AM) and peak over threshold series (POT) are selected to simulate the probability distribution of extreme precipitation. The results show that positive trend of annual maximum precipitation is detected at most of used stations, only a small number of stations are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 15 publications
1
32
0
2
Order By: Relevance
“…However, more and more studies found that the Generalized Pareto Distribution (GPD; see Pickands (1975)) could better simulate the Peak-overThreshold (POT) extreme series (Martins and Stedinger, 2001; Beguería, 2005;Xia et al, 2011;Bhunya et al, 2013;Naveau et al, 2014). Considering that the EEP events, in the current study, are defined by POT idea in term of quantiles, we employ GPD to fit the characteristics of EEP series.…”
Section: Extreme Value Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, more and more studies found that the Generalized Pareto Distribution (GPD; see Pickands (1975)) could better simulate the Peak-overThreshold (POT) extreme series (Martins and Stedinger, 2001; Beguería, 2005;Xia et al, 2011;Bhunya et al, 2013;Naveau et al, 2014). Considering that the EEP events, in the current study, are defined by POT idea in term of quantiles, we employ GPD to fit the characteristics of EEP series.…”
Section: Extreme Value Distributionmentioning
confidence: 99%
“…wheren,â, andk are the estimates of n, a, and k, respectively, and can be estimated by the L-moment method (see the detail in the literature (Hosking, 1990;Hosking and Wallis, 1997;Xia et al, 2011)). The Kolmogorov-Smirnov (KS) method at the significance level of 0.05 is used as the goodness of fit test to check the efficiency of modelling.…”
Section: Extreme Value Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a positive trend in the precipitation concentration index at most stations, but none of trends was statistically significant (=0.10). Xia et al (2012) analyzed the spatio-temporal trend of extreme precipitation events in the Huai River basin based on the daily precipitation data of 27 stations from 1960 to 2009, and they detected an insignificant (=0.05) positive trend in annual maximum precipitation at most stations.…”
mentioning
confidence: 99%